2006
DOI: 10.1038/nrd1930
|View full text |Cite|
|
Sign up to set email alerts
|

Epigenetic therapy of cancer: past, present and future

Abstract: The initiation and progression of cancer is controlled by both genetic and epigenetic events. Unlike genetic alterations, which are almost impossible to reverse, epigenetic aberrations are potentially reversible, allowing the malignant cell population to revert to a more normal state. With the advent of numerous drugs that target specific enzymes involved in the epigenetic regulation of gene expression, the utilization of epigenetic targets is emerging as an effective and valuable approach to chemotherapy as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
973
0
35

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,190 publications
(1,014 citation statements)
references
References 139 publications
6
973
0
35
Order By: Relevance
“…88,89 It has been suggested that DNA-damage encourages Ku70 to associate with the DNA-dependent kinase and move into the nucleus, leaving Bax unattended in the cytosol. Moreover, acetylation of Ku70 may also promote its dissociation from Bax, providing a possible explanation for at least one of the many proapoptotic actions of chemical inhibitors of HDACs (reviewed in Yoo and Jones 90 ).…”
Section: Mechanisms Of Suppression Of Mdpsmentioning
confidence: 99%
See 1 more Smart Citation
“…88,89 It has been suggested that DNA-damage encourages Ku70 to associate with the DNA-dependent kinase and move into the nucleus, leaving Bax unattended in the cytosol. Moreover, acetylation of Ku70 may also promote its dissociation from Bax, providing a possible explanation for at least one of the many proapoptotic actions of chemical inhibitors of HDACs (reviewed in Yoo and Jones 90 ).…”
Section: Mechanisms Of Suppression Of Mdpsmentioning
confidence: 99%
“…102,103 Relieving suppression of Bax by promoting dissociation of Ku70 represents another potential strategy for promoting apoptosis of cancer cells. HDAC inhibitory compounds reportedly induce hyperacetylation of Ku70, promoting release of Bax, 90 revealing at least one possible strategy. Cancer gene therapy interventions whereby Bax is delivered into tumors represents another approach to exploiting MDPs for cancer therapy.…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%
“…Histone lysine methylation promotes or prevents binding of proteins and protein complexes that drive particular regions of the genome into active transcription or repression [6]. MMSET has a transcriptional repressor activity, with increased H4K20 methylation gene and loss of histone acetylation.…”
Section: Introductionmentioning
confidence: 99%
“…Two of the best characterized epigenetic events are aberrant DNA methylation and changes in chromatin structure involving posttranslational modifications of histones (Yoo and Jones, 2006). Methylation of cytosines in the dinucleotide sequence CpG in gene promoters plays a role in silencing genes either by directly inhibiting the interaction of transcription factors with their regulatory sequences or by attracting methylated DNA-binding proteins, which in turn recruit transcriptional corepressors including histone deacetylases (HDACs) and histone methyltransferase, resulting in transcriptionally inactive chromatin (Galm et al, 2006).…”
Section: Introductionmentioning
confidence: 99%